PENGEMBANGAN MODEL MANAJEMEN PELATIHAN DAN PENGEMBANGAN PENDIDIKAN KARAKTER BERLOKUS PADEPOKAN KARAKTER - Maman Rachman; Masrukhi Masrukhi; Aris Munandar; Andi Suhardiyanto (Universitas Muria Kudus, 2017)
This research develops a model of characteristic training and character education management to produce academic, profession, and vocational (potential teacher and teacher) teachers who have superior competence in disseminating noble character of the nation. By using Researh and Development approach, this research uses Padepokan Character locus PPKn FIS Unnes Department. The subjects of the study were the newly graduated Unnes students, the young teachers in Semarang City and Central Java Province. The factual model of training management and the development of character education that runs so far contains weaknesses in various aspects, from planning, implementation, to evaluation of activities. On the basis of the analysis of a number of weaknesses of the factual model is then carried out the reconstruction of the conceptual model departs from the review of ethical factors and emotic factors. Conceptual model is then refined again by accommodating the results of focus group discussion with the stake holders and utilize the potential and resources owned by the character padepokan Unnes Political Education and Citizenship. This model has incorporated various aspects of the training, from the refinement of the factual model greed, the consideration of ethical factors and the emotional factors, as well as the aspirations and needs of the stake holders, so it is feasible to experiment in the wider domain.